APM konsep pecahan terpadu pendekatan Matematika realistik - Nasrullah Nasrullah; Suradi Suradi; Hamda Hamda (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Learning concept of fraction is one of the obstacles faced by teachers in schools. Through the Community Partnership Program (CPM) activities, mathematics teachers are getting involved in learning together using APM integrated concept of a realistic mathematical approach. This activity was carried out on August 24, 2019, at SMAN 5 Gowa, Gowa Regency, Tinggi Moncong District. The successful implementation of the activity supported by collaboration between the Department of Mathematics and MGMP at the junior and senior high schools of Gowa Regency. The method of implementing the activity was the training of Mathematics MGMP teachers in Gowa Regency. This training activity involved 6 participants who came from different schools including SMPN 1 Tinggimoncong, SMPN 2 Tinggimoncong, PGRI Sungguminasa Middle School, SMPN 1 Pallangga, and SMPN 5 Pallangga. In addition to teachers getting involved in receiving material and following interactive information provided during training activities, they were also asked to give responses to the activities they participated. This activity responded with enthusiasm where various activities designed in such a way as to provide a meaningful learning experience for them. The process that followed turned out to be enough to inspire them on how to learn fraction material with the integrated APM concept of a realistic mathematics approach. The impact can be looked from 2 positive changes to participants, namely directing the teacher's paradigm of learning to involve learning media and introducing the involvement of realistic mathematical approaches in learning activities.